The profitability of trading on large Lévy jumps. (17th July 2019) - Chan, Kam Fong; Gray, Phil; Pan, Zheyao
Abstract: While past research has studied the profitability of trading based on jump signals, the notion of differentiating between jumps according to their magnitude has received relatively little attention. We utilize the approach of Lee and Hannig (2010) to identify Lévy jumps and classify them as small and large. The empirical analysis shows that the arrival of large Lévy jumps provides a strong trading signal in five major equity markets. In contrast, the signal from small Lévy jumps is negligible.